1-A-D-11. Electrodiagnosis for subtypes of Guillain–Barré syndrome: A single conduction study is not enough. Issue 6 (June 2015) - Kokubun, Norito; Nagashima, Takahide; Hirata, Koichi; Yuki, Nobuhiro
<x xml:space="preserve">Abstract</x> Objective Current electrodiagnostic criteria for demyelinating and axonal forms of Guillain–Barré syndrome (GBS) may be incomplete. We evaluated serial changes in nerve conduction studies (NCSs) in GBS. Methods We reviewed NCS results on the first and second studies in 75 consecutive GBS patients. The patients were divided into two groups: anti-ganglioside antibody-positive and -negative (AGA-positive and -negative) groups. Results In the first study, 13 of 53 (25%) AGA-positive patients showed prolonged distal motor latency (DML) in the median nerve, whereas 5 of 22 (22%) AGA-negative patients had normal DMLs. In the second study, DMLs were shortened in the AGA-positive patients and significantly prolonged in the AGA-negative patients. Nine (17%) AGA-positive patients showed mildly prolonged DML in the median nerve, whereas 2 (9%) AGA-negative patients had normal DMLs. Most patients in the two groups did not show reduced motor conduction velocities (MCV) in the demyelinating range throughout the course. Interestingly, only few patients revealed prolonged F-waves in the demyelinating range. Conclusions To classify GBS into demyelinating and axonal forms, 2 sets of NCSs are required in which the median and ulnar but not tibial nerves are useful. Neither MCV nor F-wave is helpful for the classification.